An anatomic and radiographic study of medial sigmoid depression in human mandible - Asdullah, Md; Aggarwal, Anshul; Khawja, Kauser; Khan, Masood; Gupta, Juhi; Ratnakar, K (Journal of Indian Academy of Oral Medicine and Radiology, 2019)
Introduction: Medialsigmoid depression (MSD) is well-defined radiolucency in the inferior aspect of sigmoid notch seen on the few panoramic radiographs. Anatomically, MSD corresponds to a depression on medial side of upper ramus just below the sigmoid notch. The significance of this normal anatomical landmark lies in its propensity to be misinterpreted on the panoramic radiograph as a defect or a pathological entity especially a cyst. Aim and Objective: To study the prevalence of the medial sigmoid depression of mandibular ramus in dry humanmandible anatomically and radio- graphically and on panoramic radiograph of patients. Materials and Methods: The study consisted of Panoramic radiographs of the50 dry human mandibles and 50 Panoramic radiographs of adult out-patient (selected randomly) visiting the Department of Oral Medicine and Radiology was taken. The entire selected mandibles included in the study were evaluated for the medial sigmoid depression. Panoramic radiographs of the selected mandibles were made using X-Mind Pano Ceph 1800 VA (SATELEC) panoramic machine and were interpreted for the various parameterspertaining to medial sigmoid depression. Results: The medial sigmoid depression (MSD) was present among 70% of the patients and in 82% of mandibles. The findings ofMSD was similar by anatomically and radio logically among the mandibles. The presence of MSD was 27% insignificantly (P > 0.05) lower in patients compared with mandibles (RR = 0.73, 95%CI = 0.49-1.09, P = 0.16). The presence of MSD was higher among the male patients (76%) rather than in females (64%). Conclusion: The recognition of MSD was quite competent in anatomic specimen, panoramic radiograph of the specimen and patients. Its appearance may be considered as a normalvariants on the panoramic radiographs.